2008
DOI: 10.1103/physrevlett.101.247602
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Multiferroic Magnetoelectric Coupling in0.9BiFeO30.1BaTiO3

Abstract: Magnetic, dielectric and calorimetric studies on 0.9BiFeO 3 -0.1BaTiO 3 indicate strong magnetoelectric coupling. XRD studies reveal a very remarkable change in the rhombohedral distortion angle and a significant shift in the atomic positions at the magnetic Tc due to an isostructural phase transition. The calculated polarization using Rietveld refined atomic positions scales linearly with magnetization. Our results provide the first unambiguous evidence for magnetoelectric coupling of intrinsic multiferroic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
128
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 286 publications
(140 citation statements)
references
References 22 publications
7
128
4
1
Order By: Relevance
“…The anomalies in the unit cell parameters ͑a m , b m , and ␤͒ and the unit cell volume ͑V m ͒ are clearly seen at T N , confirming the distortion of the lattice accompanying the dielectric anomaly due to the intrinsic multiferroic coupling via magnetoelastic effect. 11 To summarize, our studies on the BF-0.27PT system reveal anomalies in the intrinsic value of the dielectric constant, free from any space charge contributions, and also the unit cell parameters at the AFM transition temperature ͑T N ͒ as a result of multiferroic coupling. We have also shown that the so-called rhombohedral phase of BF-xPT ͑Refs.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…The anomalies in the unit cell parameters ͑a m , b m , and ␤͒ and the unit cell volume ͑V m ͒ are clearly seen at T N , confirming the distortion of the lattice accompanying the dielectric anomaly due to the intrinsic multiferroic coupling via magnetoelastic effect. 11 To summarize, our studies on the BF-0.27PT system reveal anomalies in the intrinsic value of the dielectric constant, free from any space charge contributions, and also the unit cell parameters at the AFM transition temperature ͑T N ͒ as a result of multiferroic coupling. We have also shown that the so-called rhombohedral phase of BF-xPT ͑Refs.…”
mentioning
confidence: 69%
“…It should also be supported by other auxiliary evidence such as magnetoelastic coupling in the bulk phase through structural studies. 11 Here, we present the results of magnetization, dielectric, and structural studies as a function of temperature on 0.73BiFeO 3 -0.27PbTiO 3 ͑BF-0.27PT͒ ceramics, which reveal monoclinic distortion of the ferroelectric phase and intrinsic coupling between the AFM and ferroelectric order parameters. The particular composition ͑x = 0.27͒ that we have investigated is of special interest as it corresponds to the highest value of x closest to the morphotropic phase boundary ͑MPB͒ in the BF-xPT system 15,16 before the structure transforms to the tetragonal phase.…”
mentioning
confidence: 90%
See 3 more Smart Citations